Konsep Kepemimpinan Suami (Qiwāmah) dalam Hadis: Analisis Fikih Munakahat dan Keadilan Gender - Ali Yusuf Muzaki; Amrulloh (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
The concept of qiwāmah the husbandʼs leadership responsibility over the family is a central issue in Islamic family law (fiqh munakahat) and gender studies. Textual interpretations of hadith related to qiwāmah frequently justify male dominance and female subordination, contradicting the principles of maqāṣid syarīʼah such as justice, mercy, and public welfare. This article reconstructs the understanding of qiwāmah through an interdisciplinary approach combining hadith studies, fiqh munakahat, and Islamic gender perspectives. Using a critical literature review with a thematic (mawḍūʼī) method, six key hadith from kutub al-sittah were analyzed and compared across four classical legal schools Ḥanafī, Mālikī, Syāfiʼī, and Ḥanbalī a comparative analysis rarely conducted simultaneously in a single study. Findings reveal three core dimensions of qiwāmah: (1) leadership responsibility (kullukum rāʼin), which establishes mutual accountability rather than unilateral authority; (2) economic obligation (nafaqah) as a moral and religious duty; and (3) ethical conduct (muʼāsharah bil-maʼrūf) as the normative basis for marital harmony. Unlike previous studies focused on patriarchal critique without constructive alternatives, this article proposes mubādalah (mutual reciprocity) as a methodological framework to reinterpret qiwāmah as an ethical mandate responsive to contemporary family challenges.